Ameliorative Effects of Grewia asiatica Leaves in Animal Models of Pain and Inflammation. Issue 1 (2nd January 2023) - Singh, Atamjit; Kaur, Harpreet; Singh, Hasandeep; Singh, Balbir; Bedi, Preet Mohinder Singh; Kaur, Sarabjit
ABSTRACT: The analgesic and anti-inflammatory effects of Grewia asiatica leaf solvent extracts were evaluated in animal models. The methanol and ethyl acetate fractions prepared from the leaves showed potent analgesic and anti-inflammatory effects at 400 mg kg −1 and 100 mg kg −1, respectively. Myricetin was isolated from the ethyl acetate fraction by column chromatography. Molecular docking studies with myricetin showed a desirable binding pattern of myricetin with both COX-1 and COX-2, supporting its anti-inflammatory potential. Results showed that the anti-inflammatory and analgesic effect of methanol extract of G. asiatica leaves may be due to COX-1 and COX-2 inhibition by myricetin.